Wyznaczanie Ciężaru Slupów Kratowych Na Podstawie Parametrów Kształtu i Obciążenia - Martini, L. (Engineering Transactions, 1963)
The work is concerned with the derivation of a general formula for the weight of towers in function of their height, bending moment and transverse force. Conversely to the case of experimental formulae due to Ryle and Peterson generally applied to determine the weight of tower columns, this formula was derived theoretically by means of dimensional analysis. As has been shown, Ryle and Peterson formulae are particular cases of the derived general expressions. For single shalt tower, a particular form of the general formula has been proposed, which gives intermediate values between those following from Ryle and Peterson expressions. In further part of the work, the general formula defining the weight of anchor and dead end towers different from single shalt, was derived. Examples of numerical determination of constants occurring in proposed formulae are presented.